2019
DOI: 10.1016/j.heliyon.2019.e02375
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Co-localization of endosome markers in cells

Abstract: Clathrin mediated endocytosis is one pathway for internalization of extracellular nano materials into cells [1, 2]. In this pathway, proteins attached to receptors and the internalized materials are encapsulated in clathrin coated membrane vesicles that subsequently fuse with or transform into intracellular compartments (early and late endosomes) as their contents are being directed to the lysosomes for degradation. The following proteins are commonly used to mark the pathway at various stages: Rab5 (early end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 57 publications
(65 reference statements)
5
28
0
Order By: Relevance
“…The pink and purple spots in all four images reflect the co-localization of red with blue markers. Consistent with previous work, we observed that there are a few purple and pink spots in all images to indicate co-localization of Rab5 with Rab7, Rab11 and LAMP-1, and of Rab7 with LAMP-1 [50]. The association of PCAuNPs and Rab5 would be shown by a yellow color and the association of PCAuNPs with Rab7 and LAMP-1 would be shown by a cyan.…”
Section: Endocytosis Occurs In C2c12 and A549 Cells And Is Cell Type supporting
confidence: 90%
See 4 more Smart Citations
“…The pink and purple spots in all four images reflect the co-localization of red with blue markers. Consistent with previous work, we observed that there are a few purple and pink spots in all images to indicate co-localization of Rab5 with Rab7, Rab11 and LAMP-1, and of Rab7 with LAMP-1 [50]. The association of PCAuNPs and Rab5 would be shown by a yellow color and the association of PCAuNPs with Rab7 and LAMP-1 would be shown by a cyan.…”
Section: Endocytosis Occurs In C2c12 and A549 Cells And Is Cell Type supporting
confidence: 90%
“…Table 5 shows the averages of the auto correlation amplitude, average fitted laser beam width, and average intensity from a data set of 20-30 images of A549 cells exposed to phospholipid-coated gold nanoparticles for 1, 2, 4, and 24 h. The images show that there is a gradual increase in intensity and size of PCAuNP compartments over the 24 h. Table 5 shows the averages of the auto correlation amplitude, average fitted laser beam width, and average intensity from a data set of 20-30 images of A549 cells exposed to phospholipid-coated gold nanoparticles for 1, 2, 4, and 24 h. We observed an increasing trend of the auto correlation amplitude (g(0,0)) with time. The fit for the laser beam width ranges between 0.38-0.48 microns; this is consistent with the images shown in Figure 7 as larger size clusters were observed after 24 h. In previous work, we characterized the sizes of clathrin-mediated endocytic markers to be approximately 0.40 microns [50]. Thus, simply from this observation, one can assume phospholipid-coated gold nanoparticles may be contained in endocytic compartments.…”
Section: Phospholipid-coated Gold Nanoparticles Aggregate Significantsupporting
confidence: 88%
See 3 more Smart Citations